COMMUNICATION COMPETENCE FOR CLASS MANAGEMENT IN UNIVERSITY - Indra Novianto Adibayu Pamungkas (ENSAINS JOURNAL, 2019)
Abstract: The revolution of the industry has changed in many sectors including in Educations Field. There are generations gap that exist in higher education’s live. In the university environment there are relationships between lecturers and students. This Research aims to know what the lecturer should know about communication for class management for university level in the perspective of digital native as the students. This research used qualitative research by doing interview and Focus Group Discussion (FGD) to digital native who are study in university which based on ICT in Bandung and Jakarta.  The result show that the class management is not only what to do while the class activity but also it should be prepare before the class management. It is not only the material but also the personality of the lecturer itself. Today, the digital natives seek the information about their lecturer in social media. It becomes important thing to do because it can also bring positive effect for the relationship building. Furthermore, the personality today becomes communication. In the class management must be prepared before the class, there are preparation, personality development and knowledge development. On The class development there is a important thing that is motivation that should be built by interaction and communication between lecturer and students. Keyword: Communications, Class Management, Communication Competence